Measurements of Air Permeability and Elastic Modulus of Snow and Firn Drilled at Mizuho Station, East Antarctica - Maeno, Norikazu; Narita, Hideki; Araoka, Kuniaki (1978)
P(論文) Air permeability and elastic modulus were measured for firn samples prepared from a 20-m pit and cores drilled to the depth of 147.5m at Mizuho Station in East Antarctica. Air permeability decreased and elastic modulus increased with increasing depth or density. Two distinct changes were found at densities of 550 and 730kg・m^<-3>, i.e. at porosities of 0.40 and 0.20,in the plots of air permeability and elastic modulus against density or porosity. The former change is explained by the alteration of the densification mechanicism from mechanical packing to plastic deformation of ice particles, and the latter by the attainment of an optimum configuration of ice bonding for air permeation and mechanical strength. Observed results are compared with the theoretical air permeability of an ideal snow, to which all polar snows are considered to approach in a long ageing period under high hydrostatic pressure and high homologous temperature. It is suggested that the optimum state, which is reached at the density of 730kg・m^<-3> or the porosity of 0.20,is that of snow in which air channels are mainly located at intersections of grain boundaries and some 30 percent of them are unblocked. departmental bulletin paper